PERANAN EDMODO SEBAGAI ALTERNATIF DALAM PEMBELAJARAN DARING - Magfirah, Nurul; Nurdiyanti, Nurdiyanti; Anisa, Anisa; Thahir, Rahmatia (Jurnal Biotek, 2020)
This study aims to find out the influence of learning media of E-Learning based on Edmodo toward learning outcomes of biology students at the Muhammadiyah University of Makassar. This type of research was quasi-experimental with a pretest-posttest control group design. The population of this research was all students of fourth-semester where 45 students selected as the sample. The sample consisted of 22 students in experimental group and 23 students in control group.  The result showed that the Sig value was smaller than the level of significance (α). The hypothesis testing with t-test (independent-sample t-test) obtained a sig value was 0.006 with a significance level (α) was 0.0. It appears that there is an effect of E-Learning based on Edmodo toward student's learning outcomes of biology education at the University of Muhammadiyah Makassar.